Variations, sources, and effects on ozone formation of VOCs during ozone episodes in 13 cities in China - Shan, Danying; Du, Zhenyu; Zhang, Ting; Zhang, Xiulan; Cao, Guan; Liu, Zirui; Yao, Zhixiao; Tang, Ka; Liang, Siyuan (Frontiers in Environmental Science, 2023)
In recent years, ozone (O3) pollution has worsened in China and contributes frequently to air pollution problems. To support the implementation of coordinated control for ozone and fine particulate matter, it is essential to study the chemical compositions and sources of volatile organic compounds (VOCs), which are the crucial precursor of both ozone and fine particulate matter. In this study, 117 volatile organic compounds were monitored in 13 cities in Beijing-Tianjin-Hebei Urban Agglomeration and Fenwei plain. Concentrations of total volatile organic compounds ranged from 42 to 279 μg/m3 during the monitoring episode. In all 13 cities, alkanes, halogenated hydrocarbons, aromatics and oxygenated volatile organic compounds (OVOCs) were the dominant volatile organic compounds. Contributions of alkanes, halogenated hydrocarbons, aromatics and oxygenated volatile organic compounds to total ozone formation potential (OFP) were 21.7%–32.6%, 21.0%–27.9%, 24.3%–50.8% and 28.6%–52.3%, respectively. Furthermore, the results of source apportionment by positive matrix factorization (PMF) model indicated that solvent usage, gasoline evaporation, vehicle emissions, petrochemical industry and combustion were essential volatile organic compounds sources in 13 cities. Moreover, the sensitivity of ozone production was studied using an Empirical Kinetic Modeling Approach (EKMA) model, and it was found that ozone formation was volatile organic compounds limited in all 13 cities.